2016
DOI: 10.1111/jgh.13149
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations in patients with familial adenomatous polyposis: A systematic review and meta‐analysis

Abstract: The most frequent oral manifestation on FAP patients is osseous jaw alterations. In the future, well-designed studies are necessary to classify osseous and dental anomalies in order to demonstrate the true prevalence of each alteration separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
7
0
6
Order By: Relevance
“…The oral manifestations of FAP include osseous jaw lesions, odontomas, supernumerary teeth, unerupted teeth, and oral mucosa alteration. A recent meta-analysis showed that the frequency of osseous jaw and dental anomalies in affected individuals were 65.35% and 30.48%, respectively [14]. There has been growing interest in characterizing these alterations because they may precede CRC and may be used as an early disease diagnostic marker [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The oral manifestations of FAP include osseous jaw lesions, odontomas, supernumerary teeth, unerupted teeth, and oral mucosa alteration. A recent meta-analysis showed that the frequency of osseous jaw and dental anomalies in affected individuals were 65.35% and 30.48%, respectively [14]. There has been growing interest in characterizing these alterations because they may precede CRC and may be used as an early disease diagnostic marker [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Se estima que la prevalencia es de aproximadamente 1en 10 000 nacidos vivos. 17 Su causa son las mutaciones en la estirpe germinal en el gen APC (OMIM 611731) [15][16][17][18] y, con menor frecuencia, las mutaciones en el gen MUTYH (OMIM 604933). 15 E l g e n A P C s e e n c u e n t r a e n e l cromosoma 5q21.5, que es un gen supresor tumoral que tiene una función central en la vía de señalización Wnt.…”
Section: Displasia Cleidocranealunclassified
“…15 E l g e n A P C s e e n c u e n t r a e n e l cromosoma 5q21.5, que es un gen supresor tumoral que tiene una función central en la vía de señalización Wnt. 2,17,18 La poliposis adenomatosa familiar es el resultado de una serie de cambios genéticos, que incluyen la activación de los oncogenes o la inactivación de los genes supresores tumorales, variaciones epigenéticas, además de otros cambios cromosómicos. 19 Los factores ambientales y alimentarios pueden contribuir a la variación en la expresión clínica.…”
Section: Displasia Cleidocranealunclassified
See 2 more Smart Citations